Effect of lifelong antibiotic treatment for aortic arch prosthesis infection. (20th June 2017) - Rupprecht, Leopold; Grosse, Jirka; Hellwig, Dirk; Schmid, Christof
Abstract: A patient who underwent multiple aortic operations suffered persistent infection of the ascending aorta and arch prosthesis and was finally treated with lifelong antibiotics. An 8-year follow-up with positron emission computed tomography is reported.